Metasurface Antennas for FMCW Radar - BODEHOU, Modeste; Monnoyer, Gilles; Drouguet, Maxime; Al Khalifeh, Khaldoun; Vandendorpe, Luc; CRAEYE, Christophe (My University, 2023)
Two planar metasurface (MTS) antennas are designed to produce a pattern with optimal illumination in a radar scenario, given the a priori known path of the targets. The antennas are extremely flat, thin, with a monopole feed integrated in the plane of the structure. The monopole serves as a surface-wave (SW) launcher illuminating the slab. The excited SW progressively leaks after interacting with the MTS, forming a radiation pattern designed to cover uniformly a portion of road in a given scenario. The realized antennas radiation patterns are experimentally validated. TheMTSs are then deployed in a frequency-modulated continuous wave radar system. The experiments showed that the echo of the targets in the range-Doppler map does not statistically depend on the distance between the target and the radar, while a clear range dependence is observed when classical patch array antennas are used. That means, given the capability to engineer a particular shape for the radiation pattern and the interest for simultaneously detecting small and big targets, the MTS antennas allow one to better resolve a small and distant target, next to a big and close one.
Keywords: Beam shaping; FMCW radar; metasurfaces